FEATURES OF ICT IMPLEMENTATION IN THE PROCESS OF TEACHING RUSSIAN LANGUAGE AND LITERATURE - Saidov Zhurat Sodirovich; Gofurova Dilnora Zhaloliddinova (Web of Journals Publishing, 2025)
The article is devoted to the study of the specifics of the use of information and communication technologies (ICT) in teaching Russian language and literature. The key advantages of the introduction of ICT are considered, such as increasing students' interest in the subject, enhancing the visuality of the material and developing independent work skills. Particular attention is paid to the role of interactive tools - boards, digital textbooks, tests - in creating a productive educational environment. Examples of the use of ICT at different stages of the lesson are given, including learning new material, consolidating knowledge and preparing for exams. It is emphasized that a competent combination of technologies with traditional methods contributes to the growth of the quality of knowledge and motivation of schoolchildren, and also helps the teacher adapt to modern educational requirements.
Keywords: Digital technologies, ability, education, training, study, digital technologies, digital textbooks, knowledge, skills and abilities, thinking, to form, analysis, programs.